Kecenderungan pelukis-pelukis Sarawak menggarap imejan bercirikan Sarawak dalam karya seni tampak - Soon Mang, Ng (Universiti Malaysia Sarawak (UNIMAS), 2009)
Looking at our world today, its natural and built environment has transformed immensely as a result of global advancement and development in many facets of nation progress and sophistication of human life. Much of these environmental changes have, in one way or another influenced the perception and approach towards art among Sarawak artists'. These noticeable developments are evident in yearly art exhibitions organized by the local art associations and by CIPTA of University Malaysia Sarawak. Through personal observation, the following three rhetorical questions offer an insight on the changes of these artists' perception of the world they now view and its implication on choice of subject matter. That are include, "What are the common, if not, favorite subject matter in which Sarawak artists prefer to work-on?", "How far inclined are Sarawak artists' in selecting local subject matter in for artworks?" and ''What are the factors that influence Sarawak artists' in their selection process of local subject matter and content?" Hence, the objective of this research deduces probable conjectures to these three questions. The research objectives include, to study in-depth the development and evolution of Sarawak art movements, to analyze the artists' chosen subject matter which can be specifically categorized as typical Sarawak images and to validate the factors which influence Sarawak artists' to work on artwork with images typical of Sarawak. To achieve the objective of this research and find suppositions to the three question stated above, three methodical approaches are used in the problem-solving process. A historical method is applied by performing qualitative research on the function of museums, art galleries, art associations, and art institutions that are closely related to the development and IV evolution of art in Sarawak. Interviews with artists and personal observation of the artists' works including compiling photographic data of their artworks and , theoretical and comparative approaches, the probable factors which influence the artists' choice of subject matter and content was plausibly be achieved. The subject matter thus far indentified are figurative studies of local ethics, indigenous flora and fauna, modes of transportation, tools and equipment, native landscape, ethic costumes and other topics closely related to Sarawak culture, heritage and natural history. Furthermore, the artists' personal experience, individual interests and artistic training plays a greater influential role in choice of subject matter. Meanwhile, the artists' interaction with nature, the local environment and an intermingled modern and native lifestyle in Sarawak, stimulates their artistic vision towards documenting and advocating native subject matter. Many of the Sarawakian artists who enjoyed local and national reputation during 50's and 60's. Art in the 70's and 80's was elevated to application of media, techniques and the research of subject matter in a particular art work. During postmodernism era, 90's until now, Sarawakian artists artistic explorations in the frames of sentiments, feminism, everyday affairs, appropriation, social comment and poetic and metaphoric imagery.